True ileal mesenteric diverticula- a rare cause of intestinal obstruction (Panacea Journal of Medical Sciences, 2015)
Jejunal and ileal diverticula (Excluding Meckel’s diverticulum) are an extremely rare entity. Autopsy shows incidence of 0.5- 2.3%. Ileal diverticula consist of about 23.8% of the total cases. Although these diverticula are usually asymptomatic, serious complications such as infection, bowel obstruction, bleeding or perforation can occur. Diagnosis is often delayed due to rarity of the disease. It is often diagnosed incidentally on abdominal exploration. We present a rare case of true ileal diverticula emerging on the mesenteric border, as a cause of intestinal obstruction, in a 50 yrs old male. The patient underwent laparotomy with segmental resection of the ileum. This study is important from the perspective that though ileal diverticulum is a rare disease, it should be considered in the differential diagnosis of acute abdomen, particularly in elderly patients.